Classroom Action Research as a Tool for Teacher Reflection and Innovation in Critical Analysis of Scientific Literature (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study explores the significance of Classroom Action Research (CAR) in enhancing teacher professionalism and improving learning quality by utilizing a library research method. Drawing from various national scholarly articles spanning early childhood to secondary education, the analysis reveals that CAR serves not merely as a structured research methodology but also as a reflective pedagogical approach that cultivates teachers’ critical awareness of classroom challenges. Through CAR, educators are empowered to develop data-informed strategies, continuously assess their teaching practices, and sharpen their academic writing abilities. Moreover, the implementation of CAR fosters a research-oriented culture within schools, encouraging the integration of innovative and contextually relevant learning models into daily instruction. This research also highlights CAR’s role in promoting teachers’ autonomy and confidence in identifying problems and generating practical, evidence-based solutions. As a result, teachers become more adaptive, responsive, and professionally competent in navigating the evolving demands of the education landscape. The study concludes that CAR acts as a transformative vehicle not only for individual teacher development but also for the broader goal of educational reform. It supports sustainable improvements by aligning instructional practices with real-time classroom dynamics and the unique needs of students. Ultimately, CAR is positioned as a critical instrument for professional growth and continuous improvement that bridges theory and practice in meaningful, measurable ways, while simultaneously fostering innovation and collaboration within the educational environment. The conclusion of this study confirms that CAR is a transformative strategy that not only enhances teacher professionalism but also addresses contemporary educational challenges in a contextual and sustainable manner.